PERAN SITOKIN DALAM MEKANISME NYERI NEUROPATIK - Thomas Eko P, Purna Putra (Neurona Majalah Kedokteran Neuro Sains, 2009)
INTRODUCTION RECENTLY IT BECOME CLEAR THAT INFLAMMATORY AND IMMUNE MECHANISM BOTH IN THE PERIPHERY AND THE CENTRAL NERVOUS SYSTEM PLAY AN IMPORTANT ROLE IN NEUROPATHIC PAIN INFILTRATION OF INFLAMMATORY CELLS AS WELL AS ACTIVATION OF RESIDENT IMMUNE CELLS IN RESPONSE TO NERVOUS SYSTEM DAMAGE LEADS TO SUBSEQUENT PRODUCTION AND SECRETION OF VARIOUS INFLAMMATORY MEDIATORS THESE MEDIATORS PROMOTE NEUROIMMUNE ACTIVATION AND CAN SENSITIZE PRIMARY AFFERENT NEURONS AND CONTRIBUTE TO PAIN HYPERSENSITIVITY INFLAMMATORY CELLS SUCH AS MAST CELLS NEUTROPHILS MACROPHAGES AND T LYMPHOCYTES HAVE ALL BEEN IMPLICATED AS HAVE IMMUNELIKE GLIAL CELLS SUCH AS MICROGLIA AND ASTROCYTES